2005
DOI: 10.1182/blood-2004-08-3312
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic cell transplantation for infants with acute lymphoblastic leukemia

Abstract: The role of transplantation in infants with acute lymphoblastic leukemia (ALL) is not defined. We analyzed results of 40 infants diagnosed before age 12 months who received a hematopoietic cell transplant (HCT) between July 1982 and February 2003 in first complete remission (CR1; n ‫؍‬ 17), CR2/3 (n ‫؍‬ 7), or relapse (n ‫؍‬ 16). Patients were conditioned with cyclophosphamide with total body irradiation (n ‫؍‬ 39) or busulfan (n ‫؍‬ 1). Donors were matched related (n ‫؍‬ 8), mismatched related (n ‫؍‬ 16), or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
59
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 44 publications
12
59
1
Order By: Relevance
“…Very young children are considered particularly vulnerable patients who may not tolerate intensive treatment and hold a high risk for long-term sequelae after intensive chemotherapy, cranial irradiation and even more after hematopoietic stem cell transplantation (HSCT). 4 Whereas it is well known that infants with ALL have worse outcome than older children, 5 it was suggested that this might not be the case in AML. 6,7 During the past decade, prognosis improved not only in standardrisk (SR) but also in HR pediatric AML.…”
Section: Introductionmentioning
confidence: 99%
“…Very young children are considered particularly vulnerable patients who may not tolerate intensive treatment and hold a high risk for long-term sequelae after intensive chemotherapy, cranial irradiation and even more after hematopoietic stem cell transplantation (HSCT). 4 Whereas it is well known that infants with ALL have worse outcome than older children, 5 it was suggested that this might not be the case in AML. 6,7 During the past decade, prognosis improved not only in standardrisk (SR) but also in HR pediatric AML.…”
Section: Introductionmentioning
confidence: 99%
“…9 We recognise that the use of TBI in our approach can be challenged and that some of the toxicities observed may be attributed to the addition of this low-dose irradiation to the conditioning regimen, although doses of 1200 cGy for infants with ALL have been shown to be tolerable, albeit in a recipient with likely different comorbidities. 12 In summary, these data suggest that our conditioning regimen is feasible in the treatment of JMML. Such conditioning, although potentially curative, still carries notable risks for children with this disease.…”
mentioning
confidence: 95%
“…Unfortunately, EFS is poor for infants transplanted after relapse, and it is unlikely to improve especially for patients coming for SCT after extremely aggressive primary chemotherapy. 10,11 Children with either B-cell or T-cell ALL and specific highrisk features, for example, marked leukocytosis at presentation, hypodiploid karyotype, inadequate response to induction chemotherapy or persistent minimal residual disease, have experienced a high failure rate on contemporary chemotherapy regimens. 3 If an HLA-matched related donor is available, SCT in first remission may be a more effective approach for these very high-risk subsets.…”
Section: Sct In First Remissionmentioning
confidence: 99%
“…9 Results following SCT, from both related and unrelated donors, find that for infants in first remission, EFS ranges between 64 and 76%. [10][11][12] These infants underwent fully ablative conditioning, many receiving TBI, which increases the concern for late effects on growth and neurocognitive development. Although the risk of relapse with chemotherapy is high, it may be proposed to limit SCT to just those infants who relapse.…”
Section: Sct In First Remissionmentioning
confidence: 99%
See 1 more Smart Citation